2013
DOI: 10.1111/jcc4.12017
|View full text |Cite
|
Sign up to set email alerts
|

The New About News: How Print, Online, Free, and Mobile Coconstruct New Audiences in Italy, France, Spain, the UK, and Germany

Abstract: This paper presents cross-national research on news readership diversification. We compare written news (print and free newspapers, online and mobile news services) audiences in the 5 most populous and industrialized European countries (Italy, France, Spain, the UK and Germany). Outlining a sociodemographic portrait of these different news users is important in order to understand the changes undergone inside the world of written news. We draw on a telephone survey carried out in 2009, using a representative p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 24 publications
2
22
0
3
Order By: Relevance
“…On the one hand, this research reinforces an idea that has been pointed out in other investigations into different types of online audiences: sociodemographic variables are becoming increasingly less relevant for the discrimination of consumer behavior related to the news on the Internet (D'Haenens, Jankowski, & Heuvelman, 2004;Fortunati et al, 2014;Media Insight Project, 2014). The distinction between digital native and legacy online news brands does not succeed in activating those segmentation variables that are so important for marketing management.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…On the one hand, this research reinforces an idea that has been pointed out in other investigations into different types of online audiences: sociodemographic variables are becoming increasingly less relevant for the discrimination of consumer behavior related to the news on the Internet (D'Haenens, Jankowski, & Heuvelman, 2004;Fortunati et al, 2014;Media Insight Project, 2014). The distinction between digital native and legacy online news brands does not succeed in activating those segmentation variables that are so important for marketing management.…”
Section: Resultssupporting
confidence: 81%
“…Similar sociodemographic cohorts, with a few clear-cut categories, have been used in other studies to test different aspects of online news consumption and behaviour (e.g., Bucy, 2000;Chyi & Lee, 2013;Fortunati et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite all of this, entire media groups sell these two very different products as if they were the same. Even the readers are not the same: Fortunati, Deuze and de Luca (2013) showed that people who read news frequently on only one platform make up less than a third of newspaper readers while those who consume news frequently on at least two platforms make up forty-four percent of newspaper readership. The strategy of replacing print newspapers with an online version applied by some media groups is therefore profoundly wrong and destined to fail.…”
Section: Discussion and Conclusive Remarksmentioning
confidence: 99%
“…Westlund & Weibull, 2013;Wolf & Schnauber, 2014). Andra personliga faktorer som visat sig ha betydelse är relationsstatus och huruvida man arbetar eller inte (Fortunati, Deuze & de Luca, 2014). Därtill finns ett påtagligt samband mellan mobil nyhetskonsumtion och människ-ors övriga nyhetskonsumtion (Chan-Olmsted, Rim & Zerba, 2013) samt huruvida de använder sig av en smart mobil (Westlund, 2014).…”
Section: Användareunclassified